Robert Peel’s Tamworth Manifests and the Process of Conservative Consolidation in the First Half of 1830s - Vladimir Nikolaevich Baryshnikov; Viktor Nikolaevich Borisenko; Yulia Igorevna Kuznetcova (Управленческое консультирование, 2018)
The article is devoted to the Robert Peel’s pre-election speeches in Tamworth in 1834 and 1841. Particular attention is paid to the situation in the government and in the ranks of the Tories before the first Robert Peel’s premiership. Background of Tamworth manifests traced from the appearance of the term «conservative» in 1830. Despite the fact that the narrative is built around the Tamworth manifests, the keynote of this paper is the effect of the first parliamentary reform of 1832 . An interesting point of view is that Tamworth manifesto of 1834 was the result of the first parliamentary reform of 1832, a reaction to what happened and a glance into the future. The article describes the different points of view of historians on the Tamworth manifesto of 1834 and its role in the process of creation of the Conservative Party. Attention of authors focused on describing of the new party principles formation, in historiography called the «new conservatism». The authors showed how historians value the impact of public opinion on policy in 1830-1840-ies England. The article gives the opportunity to get acquainted with the most important apprisals of the Tamworth manifest’s role in the creation of the Conservative Party and the consolidation of conservative forces in the country. It is clear that in time, there was a review of the personal contribution of Robert Peel in these processes. Authors come to the conclusion that Tamworth manifesto of 1834 is significant, especially as the first national electoral appeal, and by the Tamworth manifesto of 1841 Robert Peel has secured the title of «founder» of the Conservative party.